2016
DOI: 10.1177/1035304616659190
|View full text |Cite
|
Sign up to set email alerts
|

Precarious work and intrinsic job quality: Evidence from Finland, 1984–2013

Abstract: It is often argued that job insecurity and precarious work are on the rise. However, the evidence to back these arguments remains mixed and inconclusive. In this study, we define and measure precarious work in Finland using five variables that reflect both objective and subjective insecurity: atypical employment, actually experienced unemployment, the threat of dismissal or unemployment, poor chances of finding a new job, and low earnings. Results based on Statistics Finland’s Quality of Work Life Surveys from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…This trend was halted by the 1990s recession, and young people's future prospects were effectively hampered by mass unemployment. In the early 2000s, normalcy was restored in the labour market, but there was no return to the exceptionally high employment rates of the 1980s (Pyöriä & Ojala, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This trend was halted by the 1990s recession, and young people's future prospects were effectively hampered by mass unemployment. In the early 2000s, normalcy was restored in the labour market, but there was no return to the exceptionally high employment rates of the 1980s (Pyöriä & Ojala, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These contracts became commonplace, creating a so‐called ‘culture of the precarious’ (Ortiz García, ). Workplace precariousness includes unemployment, short‐term contracts, part‐time contracts and low pay (Alcañiz Moscardó, ; Pyöriä & Ojala, ) and have been described as working conditions that carry the constant threat of termination (Pyöriä & Ojala, ). Work by Casanovas, Escudero Rodríguez, and Esteve () and Casanovas et al.…”
Section: Introductionmentioning
confidence: 99%
“…Considering those trends, it cannot be concluded that precarious employment in general has increased in Finland during recent years. In the same vein, Pyöriä and Ojala () show that the percentage of precarious workers in Finland did not increase significantly in the 2000s and early 2010s.…”
Section: Precarious Workers In Finlandmentioning
confidence: 88%